Collective action and “social distancing” in COVID-19 responses - Meinzen-Dick, Ruth S. (Springer, 2020)
Much of my research has been on the need for collective action in managing natural resources, and the value of groups to facilitate collective agency for women’s empowerment. Extensive research has shown that coordination among resource users is necessary to distribute rights and responsibilities for both appropriation and provision of common pool resources, such as for water withdrawals and maintenance of irrigation systems (Anderies and Janssen 2013). And we are learning about the mechanisms through which women’s groups contribute to empowerment, whether through collective enterprises (such as through self-help groups in India), access to finance, acquiring social services, or improving women’s bargaining power in their households (Brody et al. 2017). What happens, then, when people cannot come together in person because of lockdowns to prevent transmission of COVID-19? What happens to the irrigation systems in Nepal and India that need collective labor to repair them? What happens to the women who rely on weekly savings group meetings to build their financial and social capital?